Sistem Rencana Anggaran Pendidikan Berbasis Sekolah (RAPBS) di Sekolah Dasar - Sania Alfaini (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
The education budget is a supporting tool for the implementation of education in an effort to educate human resources (HR) in the region, to have the ability to be more productive and effective in developing the region, the need for funds for routine operational activities and the development of school / madrasah programs in a sustainable manner is felt by every manager. educational institutions, therefore it is necessary to have deeper research on the implementation of the education budget in SD Ta'mirul Islam. The research method used is descriptive qualitative with interview and documentation data collection techniques and using interactive analysis. The results showed that: 1) Sources of income from Ta'mirul Islam Elementary School education include: student guardians, new student admissions (PPDB), school business, government 2) The principle of income from Ta'mirul Islam Elementary School education funds uses cross subsidies, namely not all tuition fees are the same level of each student. There are two kinds of SPP that are enforced, namely SPP Standard and SPP for Community Development. 3) Determination of the priority scale of budgeting for RAPBS education activities at SD Ta'mirul Islam, as follows: Activities of teachers and regular education personnel, student activities, the rest is for the improvement of infrastructure. 4) The process of preparing the RAPBS at SD Ta'mirul Islam is as follows ; the first is to hold a coordination work meeting with all school stakeholders. Second, each stakeholder provides a budget to the school. After that, it was followed up by the treasurer and foundation committee